ANALISIS POSTUR KERJA OPERATOR INBOUND DENGAN MENGGUNAKAN METODE RULA - muhammad mansur yafi (Universitas Muhammadiyah Gresik, 2022)
Work posture is important for a worker. Wrong working posture can cause fatigue in the muscles, damage the tissue to the point of pain and discomfort. This study aims to analyze the work posture of inbound operators at PT. XYZ. This study used the Rapid Upper Limb Assessment (RULA) method. Based on the results of the research, it was found that the final score for the posture of the worker in the process of inputting goods was 7. This indicated that the condition was at a very dangerous level and action was needed to improve work posture right now. For this reason, recommendations for work postures have been made for the process of inputting goods through CATIA software with popliteal 50 and 95. Based on the results, a good inducement to apply is work posture with popliteal 50.